Sistema de informação web para o cadastro de produtores de flores e plantas ornamentais - MOREIRA JUNIOR, Maurício M. (2017)
One of the segments of Brazilian agribusiness that has grown the most in recent years was the market for flowers and ornamental plants. With the objective of elaborating a web information system, which maintains a database with information from the producers, allowing the updating of the data of the same when it is necessary, the software has been developed PeqsuisAgro, using web technologies PHP, HTML, CSS, JavaScript and the Laravel framework in conjunction with the MySQL database. Among the various functionalities are the registration and management of searches with multiple-choice questionnaires, which may be included by researchers or administrators of the software. After registering, it is possible to publish, through an internet link, the research among the producers so that they can respond. PesquisAgro proves to be an important tool for research creation and use with questionnaires between producers, since it allows the researcher to update the data of a research more quickly and with a frequency greater to the detriment of a research done in loco.